Dual Roles for PARP1 during Heat Shock: Transcriptional Activator and Posttranscriptional Inhibitor of Gene Expression - Vyas, Sejal (2013)
In this issue of Molecular Cell, Di Giammartino et al. (2012) identify a new function for PARP1 in the post-transcriptional regulation of mRNAs via ADP-ribosylation of poly(A) polymerase, a mRNA 3′ processing enzyme.